2008
DOI: 10.2174/138161208786404335
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Imaging of Prostate Cancer with Gastrin-Releasing-Peptide- Receptor Targeted Radiopharmaceuticals

Abstract: Prostate cancer is one of the most common causes of cancer in men. Evaluating the different stages of prostate cancer with conventional imaging techniques still proves difficult. Nuclear imaging might provide a technique that is able to evaluate prostate cancer, but clinical application has been limited due to lack of accuracy of current radiopharmaceuticals. The development of radiopharmaceuticals that can be targeted to specific antigens, overexpressed in prostate cancer, but sparse in normal tissue, is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 88 publications
3
62
1
Order By: Relevance
“…However, in the present study, no significant decrease in renal uptake was noted after either of these pretreatments because 213 Bi-DOTA-PESIN renal uptake is relatively low (highest tumor-to-kidney ratios among bombesin analogues; ref. 30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, no significant decrease in renal uptake was noted after either of these pretreatments because 213 Bi-DOTA-PESIN renal uptake is relatively low (highest tumor-to-kidney ratios among bombesin analogues; ref. 30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these promising results, there are potentially limiting factors that have to be taken into account when considering therapeutic applications of GRP analogues. Preliminary results in clinical studies have shown a high accumulation in the small/large intestine and relatively low uptake in tumor lesions when labeled with 99m Tc (30). The low accumulation in tumor lesions may be due to a low metabolic stability of these radiopeptides, and excretion via the hepatobiliary tract is caused by high lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Staining of normal prostate and muscle with the anti-GRPR antibody has been described in the literature by other authors [60][61][62], and at first glance, this might pose a problem for the future use of GRPR as a target for new therapeutic or diagnostic modalities. However, pre-clinical and clinical studies have shown very low uptake of GRPR-targeted bombesin-like radiopharmaceuticals in muscle with high tumor-to-muscle ratios [70].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies with PSMA as the target have been reported with encouraging results [71,72]. Bombesin-like radiopharmaceuticals, which are natural ligands of GRPR, can be relatively easy synthesized in large quantities and have shown promising results in several clinical studies [70]. However, due to its background staining, more careful selection of the protocol may be required for optimal targeting.…”
Section: Discussionmentioning
confidence: 99%
“…32 Tc-bombesin, a radioactive signal was found in the prostate tumour region within 4 min after intravenous administration of 0.7 µg 99m Tc-bombesin. 36 To 38 Cytotoxic analogues of bombesin are also being investigated because receptors for bombesin-like peptides are present on a wide variety of tumours, including prostate cancer tumours. 15 AN-215, a cytotoxic analogue of bombesin, has been shown to have a powerful inhibitory effect on the growth of PC-3 androgen-independent prostate cancers.…”
Section: Therapy With Lhrh Antagonists Backgroundmentioning
confidence: 99%